The coach-athlete relationship: a motivational model - Mageau, G. A.; Vallerand, R. J. (Journal of Sports Sciences, 2003)
The aim of this paper is to present a motivational model of the coach-athlete relationship that describes how coaches may influence athletes' motivation. In line with cognitive evaluation theory (Deci and Ryan, 1980, 1985) and the hierarchical model of intrinsic and extrinsic motivation (Vallerand, 1997, 2000), a motivational sequence is proposed where coaches' personal orientation towards coaching, the context within which they operate, and their perceptions of their athletes' behaviour and motivation influence coaches' behaviours. Also, coaches' behaviours in the form of autonomy-supportive behaviours, provision of structure and involvement have a beneficial impact on athletes' needs for autonomy, competence and relatedness, which, in turn, nurture athletes' intrinsic motivation and self-determined types of extrinsic motivation. Here, we first review coaches' autonomy-supportive behaviours. We then describe the psychological processes through which coaching behaviours have a positive influence on athletes' intrinsic and self-determined extrinsic motivation. Finally, we identify social and personality processes that determine coaching behaviours.